JUMANAZAR BAZARBAEVTÍŃ PEDAGOGIKALÍQ TÁRBIYA TARAWÍNDAǴÍ MIYNETLERINE BIR NÁZER - Joldasbaev, P. (SCIENCE and SOCIETY, 2020)
The scientific article provides detailed information about the initial pedagogical research of academician Jumanazar Bazarbaev in the field of Pedagogy in the Republic of Karakalpakstan and his scientific research with leading scientists of that period, as well as pedagogical research.